Effects of Motivational Interviewing on the Self-Efficacy of Type 2 Diabetes Mellitus Patients - Siska Puji Lestari; Titin Andri Wihastuti; Dina Dewi Sartika Lestari Ismail (Indian Journal of Forensic Medicine & Toxicology, 2022)
Diabetes mellitus is a metabolic disease that cannot be fully cured, thereby needing continuous treatment. As poor lifestyles increase in number and variation, the prevalence of diabetes mellitus is increasing every year. The purpose of this study is to determine the effects of motivational interviewing on the self-efficacy of type 2 diabetes mellitus patients. This study is an experimental study using Non-Randomized Control Group Pretest Posttest Design. The population was type 2 diabetes mellitus patients receiving treatment at Polres Tuban Polyclinic. Sample collection was performed purposively with a sample size of 58 patients. This study utilized univariate and bivariate analyses using the t-test for two dependent means. The results of statistical analyses showed the effects of motivational interviewing on the self-efficacy of type 2 diabetes mellitus patients in which there was an increase in the mean score of the intervention group from 27.3 to 36.8 (p=0.000). We concluded that motivational interviewing has an effect on improving the self-efficacy of type 2 diabetes mellitus patients.